Tensile and flexural properties of woven carbon-kenaf fiber reinforced epoxy matrix hybrid composite: effect of hybridization and stacking sequences - Yusuff, Mohamad Ikhwan; Sarifuddin, Norshahida; Mohamad Badari, Siti Norbahiyah; Mohd Ali, Afifah; Ismail, Hanafi (American Institute of Physics Inc., 2020)
Hybrid composites from combinations of synthetic and natural fibers have experienced a considerable interest among researchers due to its excellent characteristics. One of the drivers for this development owing to the ability of synthetic and natural fibers to compensate for the limitation of one another. Thus, the current effort works on the fabrication of hybrid composites from combinations of carbon fiber (C) and kenaf fiber (K) with epoxy resin using the vacuum infusion method. The stacking sequences of fibers were varied to KKKKK, CKCKC, KCKCK, and CCKCC. The effects of hybridization and stacking sequences on mechanical properties of fabricated hybrid composites were examined under tensile and flexural tests. The result shows that the tensile and flexural properties of manufactured hybrid composites were enhanced by introducing hybridization with carbon fiber. The highest tensile were obtained in the CKCKC hybrid sample, whereas, the highest flexural properties were observed in the CCKCC hybrid sample. Besides, tensile fractured and flexural modes of failures were characterized using a scanning electron microscope (SEM) and optical microscope (OM), respectively.